DEVICES COLLECTING SUNLIGHTS - Yusupov Abdurashid Khamidullayevich,; Khakimov Ulugbek ogli, (Лучшие интеллектуальные исследования, 2024)
Annotation: In this article, the geometrical design of a paraboloid concentrator that concentrates sunlight to a single focal point is considered. Such solar concentrators are distinguished by their convenience and ease of application in the public and agricultural sectors.